Liquid PTVA: A faster and cheaper alternative for generating multi-copy clones in Pichia pastoris - Aw,R; Polizzi,KM (Microbial Cell Factories, 2016)
BACKGROUND:Multiple cognate gene copy clones have often been used in order to increase the yield of recombinant protein expression in the yeast Pichia pastoris. The method of posttransformational vector amplification (PTVA) has allowed for the efficient generation of multi-copy clones in P. pastoris. However, despite its relative ease and success, this process can be expensive and time consuming.RESULTS:We have developed a modified version of PTVA, called Liquid PTVA, which allows for faster and cheaper selection of multi-copy clones. Cultures are grown in liquid medium with only a final selection carried out on agar plates, reducing overall antibiotic usage and increasing the speed of clone amplification. In addition, it was established that starting PTVA with a single copy clone resulted in higher copy number strains for both traditional plate PTVA and liquid PTVA. Furthermore, using the Zeocin selection marker in liquid PTVA results in strains with higher growth rates, which could be beneficial for recombinant protein production processes.CONCLUSIONS:We present a methodology for creating multi-copy clones that can be achieved over 12 days instead of the traditional 45 and at approximately half the cost.